Challenges associated with integrating CCA and DRR in the UK- A review on the existing legal and policy background. (2018) - Dias, Nuwan; Amaratunga, Dilanthi; Haigh, Richard
Abstract: The concept of climate change adaptation (CCA) is broad and CCA strategies aim to reduce vulnerability to expected impacts of climate change. Disaster Risk Reduction (DRR) refers to a wide range of opportunities for risk abatement and disaster management. Risk reduction includes prevention, preparedness, and part of the recovery process, and it gives particular emphasis to the reduction of vulnerability. Since both, CCA and DRR focus on reducing vulnerability and share many similarities, a number of researchers, policy makers, and practitioners have suggested integrating CCA and DRR. Even though there are many discussions on integrating CCA and DRR less is happening on the ground as there are many challenges to integrate CCA and DRR. These challenges are further increased due to the gaps in the existing legal and policy backgrounds in most of the countries. Accordingly, based on findings of a national review on the UK, conducted by a project called ESPREssO funded by the EU horizon 2020 programme, this paper reviews the challenges associated with integrating CCA and DRR in the UK while reviewing the gaps and the strengths of the existing legal and policy background in the UK for the integration of CCA and DRR. During the first phase of the study, a narrative desk based literature review was conducted. During the second stage, 15 semi-structured interviews were conducted with disaster management experts who represent both the academia and the practice. Findings reveal challenges related to governance such as institutional barriers, funding issues, challenges related to communication and challenges related to the concept of risk while demonstrating the gaps and strengths of the existing legal and policy background of the UK.